Stretching exercises in managing spasticity: effectiveness, risks, and adjunct therapies - Mostafa Mehraban Jahromi; Přemysl Vlček; Marcela Grünerová Lippertová (PAGEPress Publications, 2024)
Spasticity is a component of upper motor neuron disorders and can be seen in neurological conditions like stroke and multiple sclerosis. Although the incidence rate of spasticity is unknown, it can put pressure on the health condition of those with spasticity, and there is no absolute effective way to control it. In the past, stretching exercises were an accessible tool for physical therapists to manage and control spasticity, but opinions on the optimal dose, aftereffects, and mechanism of effects were controversial. Therefore, this article tries to provide an overview of the effectiveness and risks of stretching exercises. Furthermore, there are several adjunct therapies, such as brain stimulation and botulinum injection, that can increase the effectiveness of a simple stretch by increasing cortical excitability and reducing muscle tone and their role is evaluated in this regard. The results of this study propose that several prospective and case studies have demonstrated the benefits of stretching to control spasticity, but it seems that other methods such as casting can be more effective than a simple stretch. Therefore, it is better to use stretching in combination with other therapeutic regimes to increase its effectivity of it.